2023
DOI: 10.1021/acs.jced.3c00170
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid-Phase Equilibria of Quaternary System K+, Mg2+, Na+//Cl–H2O at 278.15 and 288.15 K

Abstract: The solid–liquid-phase equilibria of quaternary system K+, Mg2+, Na+//Cl––H2O and its three ternary subsystems K+, Mg2+//Cl––H2O; Mg2+, Na+//Cl––H2O; and K+, Na+//Cl––H2O at 278.15 and 288.15 K were studied by an isothermal solution equilibrium method. The quaternary system K+, Mg2+, Na+//Cl––H2O includes two invariant points, five univariant curves, and four crystallization regions. The double salt KCl·MgCl2·6H2O is found in the quaternary system but no solid solution. Based on the experimental results and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There have been some experimental studies that relate to the quaternary system K + , Mg 2+ //Cl – , SO 4 2– -H 2 O, as described below: the ternary system K + , Mg 2+ //Cl – -H 2 O at 273.2, , 278.2, 288.2, 298.2, 323.2, 348.2, , and 373.2 K; ternary system K + , Mg 2+ //SO 4 2– -H 2 O at 273.2, 298.2, , 318.2, 323.2, 348.2, 358.2, and 373.2 K; , ternary system K + //Cl – , SO 4 2– -H 2 O at 273.2, 298.2, 323.2, 348.2, and 373.2 K; , ternary system Mg 2+ //Cl – , SO 4 2– -H 2 O at 298.2, 303.2, 323.2, 348.2, and 373.2 K; and quaternary system K + , Mg 2+ //Cl – , SO 4 2– -H 2 O at 273.2, 288.2, 298.2, 308.2, 328.2, 348.2, and 373.2 K . The results showed that magnesium sulfate exists in a variety of hydrate crystalline forms and is prone to form a variety of double salts with potassium salts.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some experimental studies that relate to the quaternary system K + , Mg 2+ //Cl – , SO 4 2– -H 2 O, as described below: the ternary system K + , Mg 2+ //Cl – -H 2 O at 273.2, , 278.2, 288.2, 298.2, 323.2, 348.2, , and 373.2 K; ternary system K + , Mg 2+ //SO 4 2– -H 2 O at 273.2, 298.2, , 318.2, 323.2, 348.2, 358.2, and 373.2 K; , ternary system K + //Cl – , SO 4 2– -H 2 O at 273.2, 298.2, 323.2, 348.2, and 373.2 K; , ternary system Mg 2+ //Cl – , SO 4 2– -H 2 O at 298.2, 303.2, 323.2, 348.2, and 373.2 K; and quaternary system K + , Mg 2+ //Cl – , SO 4 2– -H 2 O at 273.2, 288.2, 298.2, 308.2, 328.2, 348.2, and 373.2 K . The results showed that magnesium sulfate exists in a variety of hydrate crystalline forms and is prone to form a variety of double salts with potassium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Product yield is limited by the phase equilibrium of the system. Many studies have focused on phase equilibrium in the ternary system K + , Mg 2+ //Cl – -H 2 O. Due to the presence of NaCl in the brine system, solid–liquid phase equilibria of the system K + , Na + , Mg 2+ //Cl – -H 2 O was also investigated . Besides yield, the particle size distribution is also an essential indicator for evaluating KCl production.…”
Section: Introductionmentioning
confidence: 99%